MİGREN OLGULARINDA ATAK VE ATAK DIŞI DÖNEMDE KAN ANTİOKSİDAN ENZİM DÜZEYLERİ VE GENOTİP İLİŞKİSİ - ÖZEL, SEDA (Fırat Üniveristesi, 2008)
Primer baş ağrılarının önemli bir grubunu oluşturan migren, en fazla işgücü kaybı yapan baş ağrısıdır. Migren etyopatogenezini araştıran birçok çalışma yapılmış olmasına rağmen kesin bir sonuca varılamamıştır. Son yıllarda çoğu hastalıkta olduğu gibi migren patogenezinde de oksidatif stresin önemi araştırılmaktadır.Bu çalışmanın amacı, antioksidan enzimlerden Süperoksit Dismutaz (SOD), Glutatyon Peroksidaz (GSH-Px), Katalaz (CAT), antioksidan Glutatyon (GSH) ve lipid peroksidasyon ürünü Malondialdehit (MDA)'in migren patogenezindeki rollerini araştırmaktır. Ayrıca Mangan Süperoksit Dismutaz (Mn-SOD), Glutatyon Peroksidaz-3 (GSH-Px3) ve Katalaz (CAT) enzimlerinin gen polimorfizmine bakılarak bu polimorfizmin Türk popülasyonundaki insidansını araştırmaktır.Çalışmaya 30 kadın ve 10 erkekten oluşan 40 migrenli ve 40 sağlıklı gönüllü alındı. Antioksidan enzimler (GSH-Px, CAT ve SOD), kan GSH ve plazma MDA düzeylerini, migren hastalarıyla kontrol grubu arasında ayrıca migrenli hastalarda atak ve atak dışı dönemde karşılaştırdık. Migren hastalarıyla kontrol grubu arasında, GSH-Px, CAT, SOD ve GSH düzeylerinde istatistiksel olarak anlamlı düşüklük tespit ettik (GSH, CAT için p?0.001, GSH-Px için p=0.017, SOD için p=0.04). Migrenlilerde atak ve atak dışı dönemi arasında istatistiksel olarak farklılık yoktu (p?0.05). Plazma MDA düzeyinde, migren hastalarıyla kontrol grubu arasında ve migrenlilerde atak dönemi ile atak dışı dönem arasında istatistiksel olarak fark saptamadık (p?0.05). Çalışmamızın moleküler kısmında ise; hasta ve kontrol grubu arasında Mn-SOD ve CAT genotipleri için istatistiksel olarak farklılık saptanmamışken, GSH-Px3 genotipinde anlamlı farklılık gözlendi. Üç gen için de allel frekansı açısından hasta ve kontrol grubu arasında farklılık yoktu.Sonuç olarak, migren patogenezinde oksidatif stres ve antioksidan enzimlerin rol oynayabileceğini ve verilerimize göre GSH-Px3 geni polimorfizminin en azından toplumumuz için migrene yatkınlık oluşturabileceğini düşünüyoruz.Anahtar kelimeler: Migren, Mangan Süperoksit Dismutaz, Glutatyon Peroksidaz-3, Katalaz, Polimorfizm.

Migraine, which constitutes an important group of primary headaches, is the headache that causes labor force loss the most. Although many researches have been conducted to research migraine etiopathogenesis, no exact conclusion could be reached yet. In recent years, importance of oxidative stress on migraine pathogenesis like on many diseases is being researched.The aim of this study is to research the roles of antioxidant enzymes such as Superoxide Dismutase (SOD), Glutathione Peroxidase (GSH-Px), Catalase (CAT), antioxidant Glutathione (GSH) and Malondialdehyte (MDA) of a lipid peroxidation product in migraine pathogenesis. Moreover, the incidence of this polymorphism in Turkish population is being researched by looking at the gene polymorphism of the enzymes of Manganese Superoxide Dismutase (Mn-SOD), Glutathione Peroxidase-3 (GSH-Px3) and Catalase (CAT).40 volunteers, including 30 females and 10 males, suffering from migraine and 40 healthy volunteers have been involved in this study. We compared antioxidant enzymes (GSH-Px, CAT and SOD), blood GSH and plasma MDA levels between patients who suffer from migraine and control group, and also between the attack period and initial period in patients suffering from migraine. We detected a statistically remarkable decrease in GSH-Px, CAT, SOD and GSH levels between the patients suffering from migraine and control group (for GSH, CAT p?0.001, for GSH-Px p=0.017, for SOD p=0.04). Statistically, there wasn?t any difference between attack period and initial period in patients suffering from migraine (p?0.05). As for plasma levels, we haven?t found any statistical difference between patients suffering from migraine and control group, and between attack period and initial period in patients suffering from migraine (p?0.05). In the molecular part of our study, we haven?t found any statistical difference between patients suffering from migraine and control group for Mn-SOD and CAT genotypes, but found a remarkable difference for GSH-Px3 genotype. For all of the three genes, there were no difference between the patients and control group in terms of allele frequency.Consequently, oxidative stress and antioxidant enzymes play an important role in migraine pathogenesis, and according to our data GSH-Px3 gene polymorphism cause an inclination to migraine for our regional community.Key words: Migraine, Manganese Superoxide Dismutase, Glutathione Peroxidase -3, Catalase, Polymorphism.
Relationship between blood antioxidant enzyme levels and genotype during migraine attack and initial periods in migraine cases
Keywords: Nöroloji